Intercalated PtCo Electrocatalyst of Vanadium Metal Oxide Increases Charge Density to Facilitate Hydrogen Evolution - Jingjing Zhang; Wei Deng; Yun Weng; Jingxian Jiang; Haifang Mao; Wenqian Zhang; Tiandong Lu; Dewu Long; Fei Jiang (Molecules, 2024)
Efforts to develop high-performance electrocatalysts for the hydrogen evolution reaction (HER) are of utmost importance in ensuring sustainable hydrogen production. The controllable fabrication of inexpensive, durable, and high-efficient HER catalysts still remains a great challenge. Herein, we introduce a universal strategy aiming to achieve rapid synthesis of highly active hydrogen evolution catalysts using a controllable hydrogen insertion method and solvothermal process. Hydrogen vanadium bronze HxV2O5 was obtained through controlling the ethanol reaction rate in the oxidization process of hydrogen peroxide. Subsequently, the intermetallic PtCoVO supported on two-dimensional graphitic carbon nitride (g-C3N4) nanosheets was prepared by a solvothermal method at the oil/water interface. In terms of HER performance, PtCoVO/g-C3N4 demonstrates superior characteristics compared to PtCo/g-C3N4 and PtCoV/g-C3N4. This superiority can be attributed to the notable influence of oxygen vacancies in HxV2O5 on the electrical properties of the catalyst. By adjusting the relative proportions of metal atoms in the PtCoVO/g-C3N4 nanomaterials, the PtCoVO/g-C3N4 nanocomposites show significant HER overpotential of η10 = 92 mV, a Tafel slope of 65.21 mV dec−1, and outstanding stability (a continuous test lasting 48 h). The nanoarchitecture of a g-C3N4-supported PtCoVO nanoalloy catalyst exhibits exceptional resistance to nanoparticle migration and corrosion, owing to the strong interaction between the metal nanoparticles and the g-C3N4 support. Pt, Co, and V simultaneous doping has been shown by Density Functional Theory (DFT) calculations to enhance the density of states (DOS) at the Fermi level. This augmentation leads to a higher charge density and a reduction in the adsorption energy of intermediates.